Frequency and patient attributes associated with ED visits within 30 days after discharge. (30th September 2020) - Salgado, R; Moita, B; Lopes, S
Abstract: Background: About 20%-25% of patients return to the emergency department (ED) within 30 days after inpatient discharge. This outcome is relevant since it may signal failures in inpatient care and care transitions. However, literature on the topic is still scarce. Our study aims to describe frequency and patient attributes associated with ED visits within 30 days (30d) of inpatient discharge in one public Portuguese hospital. Methods: The study included adult patients discharged in 2016. Admissions of deceased or transferred patients were excluded. The rate of 30d ED visits after discharge was computed for selected patient (gender and age) and admission attributes [urgent, Major Diagnostic Category (MDC)]. Number of days from discharge to ED visit was determined. Logistic regression was used to compute crude and age-gender adjusted odds-ratios (cOR, aOR) for each selected admission attribute. Results: From the 21744 admissions included (median age: 58y; 40% male), for 5058 there was at least one ED visit within 30d after discharge (23%). The majority of ED visits were triaged urgent (n = 2286; 45%) or very urgent (n = 1499; 30%). Time to first ED visit was, on average, 11 days. The risk of ED visit was increased among men (cOR = 1.180; 95% confidence interval - 95%CI: 1.103-1.262) and patients aged 75 or older (cOR = 1.704; 95%CI: 1.557-1.866). After controlling for gender and age differences, admissions with mental diseases (aOR = 1.807; 95%CI: 1.452-2.247), respiratory diseases (aOR = 1.786; 95%CI: 1.535-2.078), endocrine diseases (aOR = 1.758; 95%CI: 1.374-2.250) showed increased risk of visiting ED after discharge. Conclusions: ED visits after inpatient discharge are frequent and mostly due to urgent and very urgent needs. Older age, mental, respiratory and endocrine conditions are relevant patient risk factors for returning hospital for ED care shortly after discharge. Key messages: Improved quality of inpatient care and care transitions that reduce ED visits after discharge may benefit a significant part of patients. Future initiatives to reduce adverse events after discharge may target patients with older age or with mental conditions.